Fashion and methodology: the Design as a mediator (ModaPalavra e-periódico, 2016)
This article proposes a methodological analysis of the fashion collections development processes, comparing the designer and the stylist ways. It shows the main changes that the curricula of Brazil's fashion courses suffered, when they had to migrate to the design field, emphasizing the fashion design conception changes. Forthis, we investigate what we consider the first methodology for the development of fashion collections, Doris Treptow, and we compared it with the Bernd Lobach methodology and the Dijon de Moraes meta-project. The results show similarities between the methodological processes and extend their use possibilities. It was possible to realize the legitimacy of Treptow method for fashion design, and its suitability to the complex design world nowadays.
Keywords: collection development; projetual methodology; meta-project